2004
DOI: 10.1016/s1535-6108(04)00081-9
|View full text |Cite
|
Sign up to set email alerts
|

Periostin potently promotes metastatic growth of colon cancer by augmenting cell survival via the Akt/PKB pathway

Abstract: Molecular mechanisms associated with tumor metastasis remain poorly understood. Here we report that acquired expression of periostin by colon cancer cells greatly promoted metastatic development of colon tumors. Periostin is overexpressed in more than 80% of human colon cancers examined with highest expression in metastatic tumors. Periostin expression dramatically enhanced metastatic growth of colon cancer by both preventing stress-induced apoptosis in the cancer cells and augmenting endothelial cell survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
533
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 512 publications
(575 citation statements)
references
References 38 publications
40
533
2
Order By: Relevance
“…By in situ hybridisation, we identified the tumour cells as the unique source of production of periostin while immunohistochemical analysis demonstrates the presence of periostin only in the juxtatumoral stroma. This is the first report where stromal localization of periostin is described as previous studies have reported localization of periostin in the cytoplasm of other types of cancer cells (Gillan et al, 2002;Bao et al, 2004;Shao et al, 2004;Kim et al, 2005;Tai et al, 2005). Although, we have occasionally detected a cytoplasmic immunoreactivity of periostin in PDAC cells, the stromal localization was always dominant.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…By in situ hybridisation, we identified the tumour cells as the unique source of production of periostin while immunohistochemical analysis demonstrates the presence of periostin only in the juxtatumoral stroma. This is the first report where stromal localization of periostin is described as previous studies have reported localization of periostin in the cytoplasm of other types of cancer cells (Gillan et al, 2002;Bao et al, 2004;Shao et al, 2004;Kim et al, 2005;Tai et al, 2005). Although, we have occasionally detected a cytoplasmic immunoreactivity of periostin in PDAC cells, the stromal localization was always dominant.…”
Section: Discussionsupporting
confidence: 67%
“…These results are corroborated by the observation that the interaction between astrocytoma cells and big-h3, a protein homologue of periostin, is dependent on a 6 b 4 integrin (Kim et al, 2003). Previous studies reported that the a v b 3 and a v b 5 integrin complexes act as the receptors for periostin in breast, colon and ovarian cancer as well as endothelial cells (Gillan et al, 2002;Bao et al, 2004;Shao et al, 2004). These two integrin complexes are however not expressed in the majority of pancreatic tumour cell lines in vitro (data not show) and only 50% of PDAC tissue specimens express detectable levels of a v b 3 in vivo (Hall et al, 1991;Hosotani et al, 2002).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Myofibroblasts have been shown to utilize the PI3 kinase/Akt signaling pathway to avoid apoptosis in abnormal scarring [66][67][68] and periostin signaling has been shown to promote avoidance of apoptosis through this pathway [29,37]. While there was a consistent trend towards a decrease in DD cells apoptosis with periostin treatment, this did not achieve statistical significance in our in vitro collagen culture conditions (DD cells treated with vehicle vs. 0.5 ÎŒg/ml recombinant periostin, p=0.075; PF cells treated with vehicle vs. 2.0 ÎŒg/ml recombinant periostin, p=0.065).…”
Section: Discussionmentioning
confidence: 99%
“…Periostin is highly expressed during the earliest stages of bone fracture repair [15] and vascular injury [16] and periostin signaling induces the expression of molecules associated with cutaneous wound repair such as collagen and fibronectin [17,18]. A role in cancer cell metastasis has also been suggested, as periostin is a recognize component of stromal reactions in a variety of tumor types [19][20][21][22][23][24][25][26][27][28][29]. While DD shares some characteristics with each of these repair and disease processes, the role(s) of periostin in this fibromatosis is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%